Early aspects in “Aspect-Oriented Process for a Smooth Transition” - Pinciroli, Fernando (2017)
The aspect-oriented paradigm brought new expectations about building software in a modular way and improving many quality attributes, but it also came with new challenges. One of them is the lack of casuistry of its use in the industry. Software development project leaders are already facing enough risks and should not add more, such as incorporating an immature approach. Furthermore, there are no aspect-oriented proposals using standard notations and covering the full Software Development Life Cycle (SDLC). We have elaborated an alternative called Aspect-Oriented Process for a Smooth Transition (AOP4ST), that allows the smoothly incorporation of the aspectoriented paradigm in the current industrial projects and offers a complete homogenous proposal for the phases of the SDLC. In this paper, we present the first stages of AOP4ST, seeking the incorporation of the aspect-oriented paradigm in the industry with the least impact, but trying to take full advantage of the possibilities it offers.